IMPACT OF PHARMACIST INTERVENTION MANAGING DRUG RELATED PROBLEMS IN PATIENTS TYPE 2 DIABETES MELLITUS - Amirah Amirah; Ahmad Muhtadi; Siti Saidah (Farmaka, 2020)
Drug related problems (DRPs) are problems encountered often in the treatment of patients and can affect the decline of quality of life but increase disease morbidity and mortality on the other hand. From a review of 10 journals, it was found that untreated indication, adverse drug reaction, non-compliance/non-adherence, drug choice problem, dosing problem, drugs interaction, drug without indication, and drug use problem were the most common DRP experienced by type 2 diabetes mellitus patients. Pharmacists can effectively intervene in DRP through identification and prevention and physicians accept and act on these interventions. Pharmacists in their intervention on DRPs play an influential role at the prescriber level. Pharmacist intervention can also take place at both patient and drug levels. Pharmacist intervention is also capable of controlling the parameters of an objective examination to be better (lipids, blood pressure, blood sugar, etc.). Therefore, collaboration between pharmacists and other health workers needs to be pursued because it can affect the success in handling DRPs.